PENGARUH WAKTU GRADING TERHADAP KUALITAS BIJI KOPI ARABIKA - Catur Pramono; Kun Suharno; Rizky Ardhi Putranto (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Coffee production in Indonesia is currently ranked 4th in the world and in terms of quality. Temanggung is one of the coffee producing regions in Indonesia. The potential of arabica coffee in Temanggung is currently planted at an area of 5000 Ha. The population of Arabica coffee is 400 stems because it combines with other plants. To improve the quality of post-harvest arabica coffee beans, it is necessary to make a grading aid with a 3-level sieve system. This study uses three levels of sieve, namely the 1st sieve with an 8 mm hole diameter, the second sieve uses a 6 mm hole diameter and the third sieve uses a 4 mm hole diameter. Criteria for grade A coffee beans if coffee beans are mm 8 mm in diameter, grade B coffee beans if coffee beans <8 mm in diameter and ≥ 6 mm and grade C coffee beans if coffee beans are <6 mm in diameter and ≥ 4 mm in diameter.  The  best  results  of  grading  testing  for  3  minutes  resulted  in  an average criteria of 0.46 kg grade A, 0.52 kg grade B, and 0.02 kg grade C. Keywords: arabica, coffee beans, grade, grading machine